2015
DOI: 10.1371/journal.pone.0137807
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Beef by Electronic Tongue System TS-5000Z: Flavor Assessment, Recognition and Chemical Compositions According to Its Correlation with Flavor

Abstract: The aim of this study was to assess the ability of electronic tongue system TS-5000Z to evaluate meat quality based on flavor assessment, recognition and correlation with the meat chemical composition. Meat was sampled from eighteen beef cattle including 6 Wagyu breed cattle, 6 Angus breed cattle and 6 Simmental breed cattle. Chemical composition including dry matter, crude protein, fat, ash, cholesterol and taurine and flavor of the meat were measured. The results showed that different breed cattle had differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 26 publications
0
52
0
Order By: Relevance
“…According to the instructions of the e‐tongue, it could be used to describe the overall taste profiles of Dezhou‐braised chicken based on the umami, saltiness, sourness, sweetness, and astringency. Date collected by electronic tongue were calculated according to the formula as described by and the mean values of the last three cycles were used for statistical analysis (Zhang and others ).…”
Section: Methodsmentioning
confidence: 99%
“…According to the instructions of the e‐tongue, it could be used to describe the overall taste profiles of Dezhou‐braised chicken based on the umami, saltiness, sourness, sweetness, and astringency. Date collected by electronic tongue were calculated according to the formula as described by and the mean values of the last three cycles were used for statistical analysis (Zhang and others ).…”
Section: Methodsmentioning
confidence: 99%
“…found that the crude protein of pork derived from SFP is increased compared with that derived from the NSFP group. Zhang et al . indicated that the crude protein content was positively correlated with the umami taste of beef.…”
Section: Discussionmentioning
confidence: 99%
“…Water‐soluble precursors were prepared for taste evaluation according to the method of Zhang et al . with slight modifications.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a robotic system with an array of sensors that combines good reproducibility with low detection limits and high sensitivities and is thus often used for screening taste attributes (Woertz, Tissen, Kleinebudde, & Breitkreutz, 2010). During the last decade, the electronic tongue has become popular as a rapid and low-cost method for the quantitative and qualitative analyses of numerous food stuffs, including beverages (Fujita et al, 2010) and meat products (Zhang, Zhang, Meng, Li, & Ren, 2015).…”
Section: Introductionmentioning
confidence: 99%